005 Cardiac MRI: understanding myocardial motion to predict remodelling pre cardiac resynchronisation therapy. (16th May 2012) - Duckett, S G; Shi, W; Zhuang, X; Shetty, A; Ginks, M; Rinaldi, C A; Carr-White, G; Rueckert, D; Razavi, R S
Abstract : Introduction: A significant number of patients undergoing Cardiac Resynchronisation Therapy (CRT) do not remodel. Assessing global dyssynchrony has the potential to improve patient selection. We developed a framework for comparing measures of myocardial motion from cardiac magnetic resonance (CMR) imaging and evaluated the potential of these techniques to improve patient selection. Methods: 48 patients recruited, (43 males, 63.8±13.9 years), NYHA class 2.9±0.5, ejection fraction 25±9%. Patients had LBBB (QRS 154±24 ms). Acute haemodynamic response was measured at time of implant with a pressure wire in the LV measuring change in dP/dtmax . A >10% increase in LV-dP/dtmax from baseline was considered an acute response. Decrease in end systolic volume (ESV) ≥15% at 6 months was used to determine remodelling. CMR was performed prior to CRT. A novel framework was developed. Key steps included: (1) detection of heart and myocardium segmentation from anatomical CMR cine images; (2) detection of endo and epi-cardial surfaces for wall thickening computation; (3) extraction of deformation fields within the myocardium for strain computation. A systolic dyssynchrony index (SDI) was produced for all parameters which included volume change, muscle thickening, radial, circumferential, longitudinal strain and combined strain. High SDI denoted dyssynchrony. Results Pre-implant ESV 175±64 ml, post-implant ESV 155±68 ml (p<0.01). 20 (44%) patients remodelled. We found a strong relationship between volume derived SDI and acute response (p=0.008) and remodelling (p<0.001) (Abstract 005 figure 1 ). We found a weaker relationship with remodelling and muscle thickening SDI (p=0.001) and no relationship with a SDI derived from strain indexes (Abstract 005 figure 2 ). Volume SDI ≥10% was highly sensitive (0.94) and specific (0.87) for predicting remodelling. Volume SDI was far superior for predicting remodelling than any other method. The intra-observer average difference for volume SDI was 0.04±0.3% and COV was 1.8±1.2% and the inter-observer average difference was 0.55±1.4% and COV was 4.2±4.6%. Conclusion: A volume derived SDI from cine CMR strongly predicts remodelling post CRT. It is a highly reproducible measurement that has significant potential clinical implications in the future.